Pembuatan Karbon Aktif Dari Limbah Kulit Jeruk Manis (Citrus sinensis L) Sebagai Adsorben Ion Besi (Fe2+) Dalam Air Sumur - Maulida, Hikmah; Elwina, Elwina; Fachraniah, Fachraniah (Jurnal Riset, Inovasi, Teknologi & Terapan, 2023)
This research aims to utilize sweet orange peel waste as an adsorbent of Fe2+ in the form of activated carbon by reviewing the adsorbate characteristics based on absorption capacity of I2, moisture content and ash content, the effect of H2SO4 and KOH activators on adsorption capacity and removal efficiency of Fe2+ ion and adsorption kinetics of Fe2+ ion in well water samples. The fixed variable is the weight of the adsorbent, which is temperature of 315 ° C, 50 grams, particle size of 10 ± 32 mesh, volume of adsorbate 10 liters and flow rate of 4 liters / minute. The independent variable is H2SO4 and KOH activator and the adsorption time is 0; 10; 20; 30; 60; 90; 120; 150; 180; 210 and 240 minutes. The results showed that charcoal with H2SO4 activation met SNI 06-3730-1995 standards, while charcoal with KOH activation did not meet SNI standards. The equilibrium adsorption capacity (qe) for charcoal with H2SO4 activation of 0.284 mg/g occurred at 120 minutes, for charcoal with KOH activation of 0.587 mg/g occurred at 240 minutes. The highest removal efficiency of Fe2+ ions for activated charcoal H2SO4 was 91.35% and KOH 68.39%. Adsorption kinetics fulfills the second order pseudo kinetics model, which is H2SO4 activation charcoal with R2 is 0.998 and KOH with R2 is 0.9956.